Welfare of extensively managed Swedish Gotland ponies. (23rd February 2023) - Viksten, Sofie M; Hartmann, Elke; Schneller, Karin; Steen, Margareta
Abstract: It has been suggested that grazing horses could be used as a credible tool for landscape conservation which would, at the same time, improve horse welfare as opposed to conventional housing. A study was conducted between May 2014 and April 2015 on 12 one year old Gotland ponies managed extensively without supplementary feed. Monthly animal welfare assessments (n = 13) revealed welfare issues in most of the horses, i.e. low body condition score (BCS < 3/5), recurring poor skin condition in 11/12 horses and ocular discharge in 7/12 horses. At the end of the study, compared to the beginning, chafing and poor skin condition increased while coat condition improved. A correlation was found between a negative reaction (score > 0) in the human approach test and BCS < 3 and ocular discharge. Avoidance Distance test values were correlated with faecal parasite counts (> 350 eggs per gram [EPG]). These results indicate that the horses had acceptable welfare during late spring/summer (May–September) and that some horses required additional feed during winter. The animal welfare protocol proved to be an efficient tool for monitoring welfare. The results showed that factors important for extensive management are: daily monitoring; enclosures that provide sufficient feed; access to recovery enclosure; and habituation of horses to human approach.